Strategi Alokasi Sumber Daya pada Era Perbankan 4.0: Analisis Common Size laporan keuangan Bank Digital dan Hybrid - Debri Ton Mario Hutasoit; Nova Sari Manullang (Journal of Innovative and Creativity, 2026)
This research aims to analyze resource allocation strategies in the banking industry during the transformation towards the Banking 4.0 era. Amidst technological disruption, banks are required to reallocate resources from physical to digital infrastructure. The primary objective of this study is to evaluate the differences in asset and expense structures between digital banks and hybrid banks using a common size analysis approach. The research method is quantitative-descriptive. Financial statement data from digital banks (such as Bank Jago and Allo Bank) are compared with hybrid banks (such as Bank Mandiri and BCA) listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Common size results indicate that digital banks allocate nearly 80% of operational costs to IT development and digital marketing, while hybrid banks still maintain 30-40% for physical overhead. In conclusion, hybrid banks need to accelerate the downsizing of physical assets, while digital banks must optimize their promotion costs to maintain long-term financial health